Coal Criminals: Crimes of the Powerful, Extractivism and Historical Harm in the Global South - Atiles-Osoria, José M. (The British journal of criminology, 2022)
This article provides a criminological analysis of the extraction, consumption, and disposal of coal in the Caribbean and the global south. It looks at how the transnational corporation Applied Energy System (AES) and its 454-megawatt coal-fired electric power plant in Puerto Rico has manufactured a transnational network of environmental harm and violence. The paper aims to demonstrate how coloniality, law, and state-corporate deviance enable the coal sector- a habitual environmental offender- to engage in systemic harm across different jurisdictions and states of the global south. To do so, we engage with the work of scholars in the green criminology (treadmill of production), state-corporate crimes (crimes of development), and crimes of the powerful (Ecocide and Carbon Criminal) traditions. Furthermore, this article briefly describes the stories of resistance taking place in Puerto Rico. In doing so, the article describes the criminogenic practices behind this fossil fuel industry, and how it has taken advantage of colonial practices, thus enhancing the historical harm manufactured by modernity and replicated within the neoliberal economy.